2021
DOI: 10.14746/ssllt.2021.11.4.5
|View full text |Cite
|
Sign up to set email alerts
|

“I feel like it’s giving me a lot as a language teacher to be a learner myself”: Factors affecting the implementation of a multilingual pedagogy as reported by teachers of diverse languages

Abstract: To boost the foreign language learning process, language teachers need to know how to implement a multilingual pedagogy, that is, they should be able to draw on their and their students’ knowledge of other languages during lessons. This qualitative study explored the extent to which 21 foreign language teachers in Norwegian and Russian upper-secondary schools were willing and able to implement multilingual teaching practices and the factors that they thought affected this implementation. The findings revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
(67 reference statements)
1
1
0
1
Order By: Relevance
“…However, the overall findings of the research reported on are that languagesensitive teaching is still only very partially understood in Irish post-primary schools and that there is an obvious need for teacher education in this area for teaching professionals at all career stages. It has further underscored the key role that language support teachers can play in subject teacher awareness raising and skills development as part of a whole school development approach, and that school managers have a vital role to play in supporting collaborations and mentoring initiatives involving language teachers and subject teaching for such purposes to help advance this approach more widely, which supports the earlier conclusions reached by Calafato (2021). In this regard, the study has also highlighted the need for school managers to provide teaching professionals with structures for mentoring and guidance, and for data-informed analysis of practice to be included, to encourage uptake and ensure an evidence-based approach to language-sensitive teaching (Castro, Kelly & Shih 2010;Chubbuck, Clift, Allard & Quinlan 2001).…”
Section: Discussion and Concluding Commentssupporting
confidence: 63%
“…However, the overall findings of the research reported on are that languagesensitive teaching is still only very partially understood in Irish post-primary schools and that there is an obvious need for teacher education in this area for teaching professionals at all career stages. It has further underscored the key role that language support teachers can play in subject teacher awareness raising and skills development as part of a whole school development approach, and that school managers have a vital role to play in supporting collaborations and mentoring initiatives involving language teachers and subject teaching for such purposes to help advance this approach more widely, which supports the earlier conclusions reached by Calafato (2021). In this regard, the study has also highlighted the need for school managers to provide teaching professionals with structures for mentoring and guidance, and for data-informed analysis of practice to be included, to encourage uptake and ensure an evidence-based approach to language-sensitive teaching (Castro, Kelly & Shih 2010;Chubbuck, Clift, Allard & Quinlan 2001).…”
Section: Discussion and Concluding Commentssupporting
confidence: 63%
“…Hilde, likewise, reported difficulties using her multilingual competence to learn Arabic, especially grammar, linking it to difficulties making sense of grammar in the other languages in her repertoire, though she felt that knowledge of grammar terminology from French helped to some extent. Studies indicate that when teachers possess weak morphosyntactic awareness regarding the languages in their repertoires, it affects their ability to draw on their multilingualism as a resource when teaching (e.g., Calafato (2021b)). The findings of this study indicate that the same phenomenon occurs with learners and their ability to learn multilingually.…”
Section: The Effects Of Multilingual Competence On Participants' Llm ...mentioning
confidence: 99%
“…These in turn have been found to be related to such factors as teachers' knowledge of heritage language(s) of the learners or having a joint language (Haukås 2016), teachers' own plurilingual competence and plurilingual awareness (Gilham & Fürstenau 2020;Otwinowska 2017), experience in teaching migrants, a teaching area (subject), prior training in linguistically responsive teaching (Alisaari, Heikkola, Commins & Acquah 2019), prior training in multilingual pedagogy (Gorter & Arocena 2020). Apart from training and experience, certain personality characteristics seem also to play a role, such as empathising with the learner (Dewaele & Wei 2012) and being able to position oneself in the situation of the learner in order to understand his/her needs and difficulties (Calafato 2021). Furthermore, intercultural competence and intercultural sensitivity (Benett 1993) have been identified as competences that allow teachers to place themselves better in the position of the multilingual learner, and these have often been developed through living abroad (Wolff & Borzikowsky 2018).…”
Section: Teacher Agency In Socialising Multilingual Learnersmentioning
confidence: 99%